STIMULASI PERILAKU SOSIAL ANAK USIA 5-6 TAHUN DENGAN PERMAINAN KUCING DAN TIKUS DI TK NEGERI PEMBINA MENDO BARAT - Zonalisa Fhatri; Sainur Sainur; Riris Wahyuningsih (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2022)
This title was chosen because the researcher wanted to know more about the process carried out by the teacher to develop children's social behavior through cat and mouse games in class B4 of Mendo Barat Pembina Kindergarten, where traditional cat and mouse games are usually played by elementary school children. This study used a qualitative descriptive method, with data sources obtained from primary data and secondary data. The data collection technique in this research used interview, observation and documentation techniques. While the data analysis technique uses data reduction, data presentation and conclusions. Based on the results of the study that the teacher's efforts in the cat and mouse game, namely applying the habituation method and the role-playing method from the teacher's efforts, children are able to develop social behavior with children being able to play together with friends, children are able to play their roles as cats, mice and cage players to games. ends, the child is able to show an attitude of responsibility, and the child is able to show an honest attitude and the child is able to cooperate with his friends while playing.